An intriguing case of intra-osseous migration of bilateral mandibular second molars: A report of a rare entity. Issue 6 (November 2020) - Smriti, Komal; Madi, Medhini; Kumar, Mathangi; Dixit, Anmol; Arimbur, Abhay Paul; Vineetha, Ravindranath; Kudva, Adarsh; Gadicherla, Srikanth
Abstract: Intrabony migration of tooth is a rare phenomenon observed in permanent dentition when the normal eruption of the tooth is disturbed. This unusual pattern of tooth movement, which is away from the usual developmental location, is termed as ectopia. Its occurrence is commonly noted in the mandibular lateral incisors, canine and second premolars. This kind of pre-eruptive tooth movement usually occurs due to associated pathologies like cysts, tumors, or odontomes. Intrabony migration of mandibular molars is a rare occurrence, and bilateral presentation of such migration is even rarer. Here, we report such a unique entity of simultaneous bilateral migration of mandibular second molar in a 22-year old healthy male.